If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -22 + 65 = 180 Reorder the terms: -22 + 65 + 3x = 180 Combine like terms: -22 + 65 = 43 43 + 3x = 180 Solving 43 + 3x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + -43 + 3x = 180 + -43 Combine like terms: 43 + -43 = 0 0 + 3x = 180 + -43 3x = 180 + -43 Combine like terms: 180 + -43 = 137 3x = 137 Divide each side by '3'. x = 45.66666667 Simplifying x = 45.66666667
| 5=18a | | 3+x-4=7x-2 | | 2u^2+3u-20=0 | | 4*x+3=2(2x+9) | | (x-8)=x-3 | | 6+2(2-4x)=6x+2(2x-4) | | 30+40x=35 | | 55=285-10e | | 2(6x+10y)+8=0 | | 4(x-6)-10=2x | | b=11-a | | 2(x-4)-6=-6(-2x+4)-6x | | 6r+5=55 | | k+3=6+k | | 30+(.0825*30)+(15%*30)= | | 6(y+2)=-2(8y-7)+6y | | -26+26=-15p-10p | | 11x-4=5x+9 | | x*12=-2 | | X+3(4)=48 | | 3x+10=3x+4+1 | | 2(x-1)-3x=8 | | 8-2x=2x-5x | | 1x+3(4)=48 | | 9(-10)+160= | | -6h+2=-46 | | x+7=-3+3x | | .60x+.30(90)=.50(x+90) | | 6=18b | | 3x+15=12b-3b | | x*-5=10 | | 16t^2-128+400=0 |